2007
DOI: 10.1002/ijc.22845
|View full text |Cite
|
Sign up to set email alerts
|

Targeting the IGF‐1R using picropodophyllin in the therapeutical 5T2MM mouse model of multiple myeloma: Beneficial effects on tumor growth, angiogenesis, bone disease and survival

Abstract: During the last decade, a central role for insulin-like growth factor 1 (IGF-1) in the pathophysiology of multiple myeloma (MM) has been well established. IGF-I provided by the tumor-microenvironment interaction may directly and indirectly facilitate the migration, survival and expansion of the MM cells in the bone marrow (BM). The inhibition of the IGF-1R-mediated signaling pathway has recently been suggested to be a possible new therapeutic principle in MM. Using the mouse 5T2MM model, we now demonstrate tha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
73
0

Year Published

2007
2007
2013
2013

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 55 publications
(75 citation statements)
references
References 22 publications
2
73
0
Order By: Relevance
“…PPP did, however, not affect growth of established R-vsrc (IGF-1RÀ/À) tumor grafts , suggesting selectivity for IGF-1R regarding tumor growth. Furthermore, perorally administered PPP was recently shown to drastically prolong survival of a multiple myeloma mouse model, which was treated up to 150 days (Menu et al, 2007).…”
Section: Introductionmentioning
confidence: 99%
“…PPP did, however, not affect growth of established R-vsrc (IGF-1RÀ/À) tumor grafts , suggesting selectivity for IGF-1R regarding tumor growth. Furthermore, perorally administered PPP was recently shown to drastically prolong survival of a multiple myeloma mouse model, which was treated up to 150 days (Menu et al, 2007).…”
Section: Introductionmentioning
confidence: 99%
“…PPP impairs IGF-1-induced IGF-1R phosphorylation in tumor cells in vitro and in vivo, decreases Akt activity, and causes malignant cell death, leading to tumor regression Menu et al, 2006Menu et al, , 2007.…”
Section: Discussionmentioning
confidence: 99%
“…A recent study shows that PPP drastically prolongs the survival in an animal model of multiple myeloma. The animals were treated daily up to 150 days, and survival was prolonged with almost 3 months compared with the control group (Menu et al, 2007). Despite having a high antitumor efficacy, PPP is apparently also well-tolerated in vivo.…”
mentioning
confidence: 99%
“…This agent has been shown to induce tumor regression and inhibition of metastasis in several models of human cancer. [84][85][86][87] PPP does not affect the tumor growth of established xenografts composed of IGF-IR-negative cells, whereas IGF-IR-positive xenografts are fully responsive. Recent studies showed that oral PPP is well tolerated in vivo and inhibits IGF-IR expression and growth of melanomas.…”
Section: Igf-ir-targeted Therapymentioning
confidence: 95%